A dose-response and meta-analysis of phytosterols consumption on liver enzymes: Evidence from randomized clinical trials. Issue 3 (24th September 2019) - Tajik, Somayeh; Jacobson, Kevan; Talaei, Sam; Kord-Varkaneh, Hamed; Noormohammadi, Zeinab; Salehi-Sahlabadi, Ammar; Pezeshki, Mehran; Rahmani, Jamal; Hekmatdoost, Azita
Abstract : Purpose: The results of human studies evaluating the efficacy of plant Phytosterols on liver function were inconsistent. Therefore, the purpose of this paper is to eliminate these controversies about the Phytosterols consumption on liver serum biochemistry in adult subjects. Design/methodology/approach: The literatures systematically searched throughout PubMed and Scopus databases up to June 2018; it was conducted by using related keywords. Estimates of effect sizes were expressed based on weighted mean difference (WMD) and 95% CI from the random-effects model (erSimonian and Laird method). Heterogeneity across studies was assessed by using I2 index. Eighteen studies reported the effects of Phytosterols (PS) supplementation on liver serum biochemistry. Findings: The current meta-analysis did not show a significant effect on ALT (MD: 0.165 U/L, 95% CI: −1.25, 1.58, p  = 0.820), AST (MD: −0.375 IU/Liter, 95% CI: −1.362, 0.612, p  = 0.457), ALP (MD: 0.804 cm, 95% CI: −1.757, 3.366, p  = 0.538), GGT (MD: 0.431 U/L, 95% CI: −1.803, 2.665, p  = 0.706) and LDH (MD: 0.619 U/L, 95% CI: −4.040, 5.277, p  = 0.795) following PS consumption. Originality/value: The authors found that no protective or toxic effects occur after the consumption of Phytosterols on liver enzymes including ALT, AST, ALP, LDH and GGT.